Desempenho zootécnico do camarão marinho Litopenaeus vannamei (Boone,1931) cultivado com ração peletizada e extrusada - PESSÔA, Maurício Nogueira da Cruz (2008)
The statistical evaluation of the use of extruded and pelleted ration in the Litopenaeus vannamei shrimp culture, under field conditions, were done with the objective of determinie the advantages of these diets on shrimp performance index. To perform the analyses were used 481 crops, from 8 commercial farms of northeastern Brazil. It was the technique used multiple linear regression to determine the parameters of handling variables that influenced the responses of crops such as production, productivity, the conversion factor of food (FCA), the weekly average growth, the average weight end, the quantity of feed consumed and survival. These responses were measured by the density of storage, but also in time of cultivation. It may be noted that there was no significant difference (P ≥ 0,05) between the use of feed on the variables average weight final and average weekly growth, as in other variables can be observed that for the storage density of 15 shrimps.m-2 there were differences of up to 20.1% in the FCA in favour of extruded ration, a production 9.7% higher when using pelleted ration of feed consumption and a 33.2% higher in pelleted feed. For densities of 60 shrimps.m-2 the difference in the FCA was 18.8% lower when you used to feed pelleted, production was 7.2% higher if using pelleted diet, consumption of feed was 8.5% lower when used if pelleted diet and productivity was 10.3% higher when the extruded feed was used for that density.